2006
DOI: 10.1002/nau.20345
|View full text |Cite
|
Sign up to set email alerts
|

Sacral nerve stimulation for voiding dysfunction: One institution's 11‐year experience

Abstract: Aim: The purpose of this study was to review our institution's 11-year experience with SNS for the treatment of refractory voiding dysfunction. Dating back to 1993, it covers a span of time which describes the evolution of SNS as it includes PNE trials, non-tined (bone-anchored or fascial-anchored) leads, percutaneous tined leads with two-staged procedures, and even percutaneous pudendal trials. Methods: A retrospective review was performed on SNS patients who received an implantable pulse generator (IPG) in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
4
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 27 publications
3
86
4
3
Order By: Relevance
“…Hence, an SNM evaluation should be considered for incomplete SCI patients with overactive bladder syndrome in case of anticholinergic failure, as well as for SCI subjects with non-obstructive urinary retention. 11,12 However, in our sample, the percentage occurrence of late failures in urinary retention subjects because of loss of efficacy (30.7%) is to be taken into account, even though all patients developing device failure responded to controlateral Sacral neuromodulation in SCI patients G Lombardi and G del Popolo sacral S3 lead placement. In addition, SNM is safe; in fact, the percentage of adverse events was low overall, and all were treated effectively with only five cases necessitating surgical intervention.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, an SNM evaluation should be considered for incomplete SCI patients with overactive bladder syndrome in case of anticholinergic failure, as well as for SCI subjects with non-obstructive urinary retention. 11,12 However, in our sample, the percentage occurrence of late failures in urinary retention subjects because of loss of efficacy (30.7%) is to be taken into account, even though all patients developing device failure responded to controlateral Sacral neuromodulation in SCI patients G Lombardi and G del Popolo sacral S3 lead placement. In addition, SNM is safe; in fact, the percentage of adverse events was low overall, and all were treated effectively with only five cases necessitating surgical intervention.…”
Section: Discussionmentioning
confidence: 97%
“…Most published studies, including those for FDA approval, are of relatively short duration (Ͻ1-2 years). Latini et al 44 reported that 90% of patients maintained a 50% reduction of urge incontinence symptoms (median follow-up, ϳ1 year), and Siegel's group 45 reported that ϳ70% of their patients indicated an improvement of Ͼ50% (mean follow-up, 22 months). In women with retention due to Fowler's syndrome, nearly 80% of patients implanted were reported to have persistent benefit, 46 although 54% had required revision procedures.…”
Section: Figmentioning
confidence: 99%
“…With a mean follow up of 22 months (range 3-162 months), sustained subjective improvement was >50%, >80%, and >90% in 69%, 50%, and 35% of patients, respectively. By QOL survey, 60.5% of patients were satisfied with current urinary symptoms (Sutherland et al, 2007).…”
Section: Clinical Efficacymentioning
confidence: 98%